Penyuluhan Tentang Ileus Obstruktif dan Kompres Hangat di RSUD Dr. Soeselo Kabupaten Tegal - Ahmad Zakiudin; Tati Karyawati; Naila Naila (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Obstructive ileus is a digestive system disorder characterized by a blockage caused by abnormalities in the intestinal lumen, intestinal wall, or foreign objects outside the intestine. Blockages in this intestinal area can cause accumulation or buildup at the site of the blockage. Patients with obstructive ileus generally experience complaints such as nausea, vomiting, abdominal distension, bowel disorders, flatus (gas) disorders, and the most common symptom is abdominal pain. The goal of this community service is to enable families to understand the definition, causes, and management of obstructive ileus and to practice applying warm compresses to minimize pain in the affected area. The methods used in this activity were counseling, interactive discussions, and practice of applying warm compresses. The media used were leaflets and flipcharts. The results obtained from this health education activity can improve patient (family) knowledge and practice in applying warm compresses to relieve pain. It is hoped that after this activity, patients (families) can apply knowledge of how to manage pain independently as an initial preventative measure to reduce pain